Mechanisms of transposable element transcript dysregulation in brain aging and Alzheimer's disease - McEntee, Cali Madison, author; LaRocca, Thomas J., advisor; Lark, Daniel S., committee member; Moreno, Julie A., committee member; Tjalkens, Ronald B., committee member (Colorado State University. Libraries, 2025)
Transposable element (TE) transcript accumulation may significantly contribute to neuroinflammation in brain aging and Alzheimer's disease; however, the mechanisms underlying TE dysregulation in this context have not been well characterized. The studies in this dissertation investigate two possible causes of TE dysregulation: 1) reduced expression and/or activity of the adenosine deaminase acting on RNA 1 (ADAR1) enzyme; and 2) increased chromatin accessibility in repressed regions of the genome. Guided by my mentoring team, I investigated these hypotheses in various experimental models and datasets throughout four studies. First, I examined changes in inflammatory signaling and TE transcript expression with ADAR1 suppression in primary human astrocytes. Second, I attempted to upregulate ADAR1 in the brains of older mice to prevent age-related cognitive decline and neuroinflammation. Third, I identified TE transcripts that form double-stranded RNA in the absence of ADAR1, and those that are most likely to stimulate inflammation, through cell culture experiments and RNA immunoprecipitation analyses. Finally, I analyzed cell-type-specific changes in TE transcript expression and chromatin accessibility in Alzheimer's disease using prefrontal cortex single-nucleus RNA-seq data. These studies also addressed the potential pro-inflammatory signaling pathways activated by TE transcripts, potentially driving neuroinflammation with brain aging and Alzheimer's disease. In summary, this work may serve as a foundation for future studies examining mechanisms of TE transcript dysregulation, and it suggests potential therapeutic targets to modulate their expression.
Keywords: Alzheimer's disease; dsRNA; transposable elements; astrocytes; ADAR1; scRNA-seq